The linguistic image of abortion and the foetus–child opposition. A lexical analysis of Polish press texts in electronic media in the first two decades of the 21st century (2000-2018) - Szczepkowska, Małgorzata (Protection of human life at the prenatal stage of development: Social, medical and legal aspects, 2026)
The chapter analyses abortion vocabulary in Polish journalistic media from 2000 to 2018, using qualitative and quantitative methods. It examines the foetus-child opposition arising from whether the nasciturus is granted human status, engaging with prior research on this vocabulary.The analysis shows that the opposition underlies two linguistic repertoires, the use of which situates the speaker on one side of the ideological dispute. Comparing abortion texts with texts on pregnancy, motherhood, and miscarriage reveals that across all texts on the prenatal stage of development, the nasciturus is called a "child" more than three times as often as a "foetus.""Child" thus emerges as the preferred designation for the unborn, while the linguistic status assigned to the nasciturus depends on context, even in the leftist-liberal press: "child" in texts on pregnancy or miscarriage, "foetus" in texts on abortion.